2013
DOI: 10.5114/ceji.2013.34353
|View full text |Cite
|
Sign up to set email alerts
|

Experimental immunology Potential role of RING finger protein 166 (RNF166), a member of an ubiquitin ligase subfamily, involved in regulation of T cell activation

Abstract: RING (really interesting new gene) finger protein 166, or RNF166, belongs to a C3HC4 ubiquitin ligases subfamily, which include four related proteins containing a conserved C3HC4 (Cys3-His-Cys4) RING finger domain. RNF125, one member of the subfamily, has been identified as a regulator of T cell activation, but the potential roles of another member RNF166 remains poorly understood. Here we reported that RNF166 is involved in regulation of T cell activation. Flow cytometry (FCM) data showed that overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Similarly, with its paralogue RNF125, LjRNF114, as a member of the RING-UIM family, contains an N-terminal RING finger domain, three zinc fingers (a C2HC domain and two C2H2-type zinc fingers) and a C-terminal UIM (39). In this study, we confirmed that LjRNF114 possessed ubiquitin E3 ligase activity, and UIM and RING domains were important for LjRNF114's ubiquitin ligase activity, which is consistent with previous studies (18,40). Lin et al (21) demonstrated that the E3 ligase activity of RNF114 is responsible for its regulating effect on immune response.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, with its paralogue RNF125, LjRNF114, as a member of the RING-UIM family, contains an N-terminal RING finger domain, three zinc fingers (a C2HC domain and two C2H2-type zinc fingers) and a C-terminal UIM (39). In this study, we confirmed that LjRNF114 possessed ubiquitin E3 ligase activity, and UIM and RING domains were important for LjRNF114's ubiquitin ligase activity, which is consistent with previous studies (18,40). Lin et al (21) demonstrated that the E3 ligase activity of RNF114 is responsible for its regulating effect on immune response.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have identified that the RING-UIM family members, including RNF114, RNF125, and RNF166, positively regulate T cell activation. 33,[314][315][316] These three members act as the positive regulators of TCR signaling-mediated T cell activation, using surface CD69 expression as a surrogate marker for cell activation. Silencing the RNF125 dramatically suppresses T cell activation in response to TCR cross-linking, and overexpression of RNF114 and RNF166 significantly upregulates the CD69 expression.…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%
“…Recently, other members including RNF166 and RNF114 were reported subsequently. The overexpression of RNF166 in primary T cells and Jurkat T cells induces over 2-fold increase of CD69, a T-cell activation marker, suggesting that RNF166 is also a positive regulator of T cell activation ( 89 ). RNF114 is a novel positive regulator of T cell activation, in which the C 2 H 2 domain is involved in this process ( 90 ).…”
Section: Host Ring E3s As Immune Regulatorsmentioning
confidence: 99%